1995
DOI: 10.1074/jbc.270.31.18428
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the T-cell Antigen Receptor (TCR) Induces Association of hSos1, ZAP-70, Phospolipase C-γ1, and Other Phosphoproteins with Grb2 and the ζ-Chain of the TCR

Abstract: Signaling by the T-cell antigen receptor (TCR) involves both phospholipase C (PLC)-gamma 1 and p21ras activation. While failing to induce Shc/Grb2 association, ligation of the TCR/CD3 receptor in Jurkat T-cells induced hSos1-Grb2 complexes. In addition to hSos1, Grb2 participates in the formation of a tyrosine phosphoprotein complex that includes 145-, 95-, 70-, 54-, and 36-38-kDa proteins. p145 was identified as PLC-gamma 1 and p70 as the protein tyrosine kinase, ZAP-70. Although of the same molecular weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…However, it has recently been shown that the Grb2/mSos association is also regulated by intracellular signals. For instance, stimula-tion of the EGF receptor [34] or the T cell receptor complex [35,36] increased the association of Grb2 with mSos. The enhancement of the complex formation of ACK with Grb2 following EGF stimulation may be due to a conformational change of the complex upon the binding of Shc to Grb2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been shown that the Grb2/mSos association is also regulated by intracellular signals. For instance, stimula-tion of the EGF receptor [34] or the T cell receptor complex [35,36] increased the association of Grb2 with mSos. The enhancement of the complex formation of ACK with Grb2 following EGF stimulation may be due to a conformational change of the complex upon the binding of Shc to Grb2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Grb2 is an adaptor protein that mediates signaling from c-Met to Ras via recruiting the guanine nucleotide exchange factor (GEF) Sos (Boguski and McCormick, 1993). The Grb2 complex as it is formed in cells was reconstituted on GST-Grb2 beads in vitro as shown previously (Nel et al, 1995). The specificity of this reconstitution was demonstrated in that the association of c-Met, Gab1, Shp2, and Ras to GST-Grb2 was predominantly observed upon HGF induction in CD44v6-expressing cells ( Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although PLC-␥1 has been detected in complexes with the CD3 components of the T cell receptor (30), with the T cell-specific nonreceptor PTKs (Lck, Fyn, and ZAP-70) (31)(32)(33), and with LAT (34), the physiological binding targets of the SH2 domains of PLC-␥1 and the PTK responsible for the phosphorylation of PLC-␥1 during T cell activation remain unknown.…”
Section: Discussionmentioning
confidence: 99%